Development and Assessment of Chicken Fortified Papad - Sakunde, Deepali T; Gangwar, Mukesh; Bhong, Chandrakant D; Barate, Abhijit K; Bhalerao, Sanjay M (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was conducted to standardize formulation and processing conditions for chicken fortified papad. Deboned, pressure cooked  chicken was dried in a hot air oven at 60°C for 12-15 h ground to powder, and used in this study. The formulation was standardized with cooked  mashed potato, tapioca flour, cumin seeds, red chilli powder, oil and salt. Different levels of chicken powder (0, 10, 20, and 30%) were used to  replace the cooked smashed potato and tapioca flour from the standard formulation. The papads were dried in a hot air oven at 50°C for 1 h.  The quality of chicken fortified papad was evaluated based on proximate composition and sensory evaluation. Protein, fat, crude fibre and ash  percentage of fortified papad recorded a significant increase with the increase in the level of chicken powder. Moisture percent recorded a  significant increase in the chicken fortified papad to that of control. The sensory scores of deep-fried papads for all attributes, i.e., appearance,  flavour, crispiness and overall acceptability of control and chicken fortified papad with 20% chicken powder were comparable.
Keywords: Chicken fortified Papad; Chicken powder; Crude fibre; Potato; Tapioca flour